The Value of β‐Blockers Administration during Recovery Phase of Dobutamine Stress Echocardiography: A Review. Issue 6 (8th April 2013) - Nguyen, James; Juneman, Elizabeth; Movahed, Mohammad Reza
<x xml:space="preserve">Abstract</x> Dobutamine stress echocardiography (DSE) is a successful technique for detection of ischemia in patients with suspected coronary artery disease (CAD). There are some data that administration of β‐blocker after peak infusion of dobutamine can improve sensitivity. The goal of this manuscript is to review the current literature in regard to the mechanism and accuracy of post–dobutamine β‐blocker administration for ischemia detection. In this review, we present 2 case reports followed by detailed review of the literature.